"I hope you've washed your hands": the rebirth of the untouchable. Issue 4 (1st October 2020) - Rajadhyaksha, Ashish
ABSTRACT: Can the "social" aspect of "social distancing" reinvent segregation? This has become an urgent question as a new era dawns in the organization of public behaviour. As touch reoccupies its central role in defining sociality, a raft of social regulations go hand-in-hand with the promise of a new sanitized and touchless existence. Both are designed to keep "us" at distance from the new frontlines of "them": produce barriers that keep at bay a contaminating amalgam of essential service workers, urban protesters and migrants. Recent work in India around the practice of caste explores a complex phenomenology of touch, how it works, what it means, and how it is systematized to define an Other, that may have larger relevance in the barricades of protection we see everywhere in the pandemic. We may also see a resistance to a globalized unitary order defined by the possible return of radical touch : in the return to offline, in physicality of Occupy movements, and in new political and economic frontlines that might also see the rebirth of the proverbial untouchable.